Family Meals Experiences Families with Adolescents: A Descriptive of Literature Review - Wanich Suksatan; Bovornpot Choompunuch; Vachira Posai (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background Family meals play an important factor in family relationships and are considered as a symbolof family communication. Family meals were associated with increased dietary consumption and improvedpsychosocial health. However, few studies have focused on the experience of eating together as a family.The aim of the current literature review was to explore the benefits and challenges of eating together as afamily, and how family members adopt and modify family meals from their childhood experiences.Methods Studies were included if the researchers examined family meals or family dinners or family Mealsexperiences of families with adolescents; nine articles met the criteria. The studies published between 2010and 2019 taken from Scopus, PubMed, and CINAHL databases.Results This literature review of family meals provides an understanding of parents’ and children’sexperience in the family meals. The results are divided into three themes including: 1) childhood familymeal experience; 2) the role and responsibility of family members; and 3) family perception.Conclusion Parents’ childhood experiences influenced the types of food, norms, and cultures, that the familydisplayed at current meals. The family roles and responsibilities had changed from the past. Parents triedto preserve the family meals as an opportunity to connect the present with past experiences. Parents couldspend this period interacting with their children and transmitting the norms and culture to the next generation.